Wnt signaling directs human pluripotent stem cells into vascularized cardiac organoids with chamber-like structures - Liang, Po-Yu; Chang, Yun; Jin, Gyuhyung; Lian, Xiaojun; Bao, Xiaoping (Frontiers in Bioengineering and Biotechnology, 2022)
Heart diseases are the leading cause of death around the world. Given their unique capacity to self-renew and differentiate into all somatic cell types, human pluripotent stem cells (hPSCs) hold great promise for cardiovascular disease modeling and drug screening. hPSC-derived cardiac organoids are emerging biomimetic models for studying heart development and cardiovascular diseases, but it remains challenging to make mature organoids with a native-like structure in vitro. In this study, temporal modulation of Wnt signaling pathway co-differentiated hPSCs into beating cardiomyocytes and cardiac endothelial-like cells in 3D organoids, resulting in cardiac endothelial-bounded chamber formation. These chambered cardiac organoids exhibited more mature membrane potential compared to cardiac organoids composed of only cardiomyocytes. Furthermore, a better response to toxic drugs was observed in chamber-contained cardiac organoids. In summary, spatiotemporal signaling pathway modulation may lead to more mature cardiac organoids for studying cardiovascular development and diseases.